MOLECULAR CHARACTERIZATION OF ANISAKID NEMATODES IN FISHES OF NORTHERN SARDINIAN SEA - T. Tedde; M.C. Piras; P. Merella; P. Mele; G. Lorenzoni; M.N. Rosa; S. Salza; A. Assaretti; F. Santoru; E. Marongiu; S. Virgilio (Italian Journal of Food Safety, 2012)
The authors report results of analysis carried out during 2008-2010 for identification and molecular characterization of larval Anisakis nematodes isolated from fishes of the northern Sardinian sea.